2000
DOI: 10.1038/sj.ejcn.1601055
|View full text |Cite
|
Sign up to set email alerts
|

The use of the Mini-Nutritional Assessment (MNA) tool in elderly orthopaedic patients

Abstract: Objective: To assess the use of the Mini-Nutritional Assessment (MNA) in elderly orthopaedic patients. Design: An observation study assessing the nutritional status of female orthopaedic patients. Setting: The orthopaedic wards of the Royal Surrey County Hospital. Subjects: Forty-nine female patients aged 60 ± 103 y; dietary records were obtained for 41 subjects and 36 subjects gave a blood sample for biochemical analysis. Major outcome methods: MNA questionnaire, anthropometry, plasma albumin, transferrin, C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
98
3
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 10 publications
6
98
3
5
Order By: Relevance
“…CI ¼ confidence interval; eBMI ¼ body mass index (kg/m 2 ) using stature estimated from knee height (Chumlea et al, 1985). (Murphy et al, 2000) and 5800 kJ/day (Bastow et al, 1983). The varied criteria used to define undernutrition are a likely factor for this large variation in findings.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CI ¼ confidence interval; eBMI ¼ body mass index (kg/m 2 ) using stature estimated from knee height (Chumlea et al, 1985). (Murphy et al, 2000) and 5800 kJ/day (Bastow et al, 1983). The varied criteria used to define undernutrition are a likely factor for this large variation in findings.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary energy intake of the undernourished participants in this study was approximately 4000 kJ/day. In the three studies that have reported selecting participants to be undernourished and have documented dietary energy intake while patients were in the acute care setting (Bastow et al, 1983;Volkert et al, 1996;Murphy et al, 2000), findings have been inconsistent with values ranging between 2950 Nutritional status was assessed upon receiving consent to participate in the study (range: day 2 to day 6 postfracture). Energy and protein intake averaged over 3-5 consecutive days (n ¼ 10, n ¼ 10, n ¼ 48 with 3, 4 and 5 days intake data, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations